2019
DOI: 10.14527/pegegog.2019.037
|View full text |Cite
|
Sign up to set email alerts
|

Examining test anxiety in terms of academic expectations stress and motivation to study

Abstract: The purpose of the study was to examine the relationship between the exam anxiety level of middle school students, their academic expectations stress, and level of motivation to study lesson. The study group consisted of 364 (184 female and 180 male) 7th and 8th grade secondary school students. Three instruments were used for data collection; Academic Expectations Stress Inventory, Motivation to Study for Adolescences Scale and Exam Anxiety Scale. Exam anxiety was chosen as dependent variable while academic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…The High Anxiety profile also scored significantly higher in PI, E, and B but, in this case, with large effect sizes. This finding is consistent with the positive and significant correlations found between anxiety and school-based distress in previous literature (e.g., [35,36,43]) and in this study, evidencing that students with high levels of anxiety tend to be more sensitive to stressors in the school setting and to manifest distress symptoms. Likewise, the present work provides interesting information from the person-centered approach used.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The High Anxiety profile also scored significantly higher in PI, E, and B but, in this case, with large effect sizes. This finding is consistent with the positive and significant correlations found between anxiety and school-based distress in previous literature (e.g., [35,36,43]) and in this study, evidencing that students with high levels of anxiety tend to be more sensitive to stressors in the school setting and to manifest distress symptoms. Likewise, the present work provides interesting information from the person-centered approach used.…”
Section: Discussionsupporting
confidence: 93%
“…The results revealed a positive and significant association between each form of anxiety (i.e., AA, SA, and GA) and each source (i.e., TI, AS, PI, ASC) and manifestation (i.e., E, B, PH) of distress. This finding corroborates Hypothesis 1 and is in line with previous works that identified positive and significant correlations between school-based distress and anxiety [25][26][27][28][29][30][31][32][33][34][35] and between school-based distress and two different forms of anxiety: school anxiety [42,43] and test anxiety [10,[36][37][38][39][40][41]. It should be noted that this research revealed a small magnitude for all correlations, except for the association of AA, SA, and GA with the emotional manifestation of school-based distress, which showed a moderate magnitude.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This situation may result in back and neck pain, headaches, insomnia, and social withdrawal (Feld & Shusterman, 2015; Galloway et al, 2013). Academic stress increases test anxiety (Çelik & Yıldırım, 2019), and reduces psychological resilience (Wilks, 2008) and subjective well‐being (Choi et al, 2019). When examined from this perspective, academic stress increases the risk factors for negative psychological impacts on students and reduces protective features.…”
Section: Discussionmentioning
confidence: 99%